New Trends in Databases and Information Systems : ADBIS 2020 Short Papers, Lyon, France, August 25–27, 2020, Proceedings /: ADBIS 2020 Short Papers, Lyon, France, August 25–27, 2020, Proceedings. (2020) - Unknown
No abstract available